KARAKTERISTIK KIMIAWI FLY ASH BATU BARA DAN POTENSI PEMANFAATANNYA SEBAGAI BAHAN PUPUK ORGANIK - Sari Widya Utami (AGROINTEK, 2018)
The purpose of the research was to study the content of chemistry of fly ash and the its potention of fly ash as the matterial of organic fertilizer. The research was conducted by mixing fly ash with some organic matterials  with comparison 1:9. The element content of organic fertilizer was compared to the quality  standard of organic fertilizer based on Government Regulation. The result of the research showed  that the adding of fly ash  could  increase the value of pH and it did not increase  some macro nutrients and the heavy metal content.